Perancangan Controlling System Keamanan Berbasis Arduino Menggunakan Kamera Internet Protocol - Ridwan Ridwan; Asmaul Husna (Fakultas Teknik, 2020)
The act of theft is an act carried out without being known by the owner. It takes vigilance in maintaining security at home, shops, buildings and other places. This study discusses how to design a room security system equipped with sensors placed at the entrance or at other locations that are equipped with security system applications. The study used ultrasonic sensors mounted on the door of the room and the Arduino microcontroller as a tool to process and the buzzer that functions to issue a warning sound. Cameras IP used to display indoor images and website applications to display and control streaming. The application works to detect when there is a movement approaching at a certain distance to the sensor. When there is a movement, the sensor will send a signal to Arduino and then Arduino sends a notification to the user. Users receive phone call notifications and can view room conditions through camera access on the website application. Website application is equipped with a control menu display that functions to turn on and off the alarm. The system prototype can send notifications to users via mobile phones if there is movement in a room with an IP camera.